Development of Short Film-Based Muhadasah Learning Media at SMP IT LHI Yogyakarta - Rita Octavia; A. Hasan, Adtman (Language Development Center, 2023)
Background: Muhadasah can be interpreted as how students express ideas in Arabic through conversation, where the conversation is carried out between students and teachers or between students and other students. However, the muhadasah learning process is generally less innovative and fun. Teachers often use the lecture method by displaying vocabulary and asking students to recite and memorize it. In learning muhadasah, it is best to use interesting media that motivate students to be active or make it easier for them to learn muhadasah. Purpose: It aims to develop a short film–based muhadasah learning media, to know the feasibility of these media and to find out the response of LHI IT Junior High School students to these learning media. Method: This type of research is development research. The development of short film-based muhadasah learning media is carried out through several stages, namely 1) finding potentials and problems at the time of learning observation and interviews, 2) spreading needs analysis questionnaires, 3) designing learning media product, 4) asking for material expert responses, 5) revising products based on expert responses, 6) product trials in the classroom. Results and Discussion: The research results in muhadasah learning media products based on short films at SMP IT LHI Yogyakarta. The sampling and samples were determined from 30 students participating in muhadasah learning and one Arabic language teacher. Conclusions and Implications: It can be concluded that short film-based muhadasah learning media is very suitable for use. Based on an expert assessment of learning media, a feasibility score from a material expert was obtained at 4.8 with an SB category ( excellent). At the same time, the feasibility score from the design expert was 4.7 with the SB category (outstanding). Students' response to short film-based muhadasah learning media products was very feasible, with an average score of 4.27 on the material aspect and a 4.3 on the design aspect.